THE VALUE OF VITAMIN D IN HUMAN PATHOLOGY - N. V. Skripchenko; M. A. Buhalko; L. A. Alekseeva; E. Ju. Skripchenko (LLC "Diagnostics and Vaccines", 2017)
This review article presents the current data on vitamin D metabolism, «classical» and «nonclassical» functions which are most widely studied in recent years. Vitamin D inhibits cell proliferation and stimulates cell differentiation, inhibits adaptive immunity and promotes innate immunity. In recent years, proven the impact of vitamin D on the development and functioning of the nervous system, including the process of myelination. These effects can largely determine the role of vitamin D in the prevention and for a number of widespread diseases of modern man, including infectious pathology, autoimmune diseases, neuropsychiatric disorders, which explains the necessity of studying the therapeutic potential of vitamin D in a variety of human pathology.